Особливості клінічного перебігу і шляхи удосконалення лікування кишкових інфекцій у дітей на сучасному етапі - Ольховська, Ольга Миколаївна; Ольховская, Ольга Николаевна (My University, 2011)
The main clinical peculiarities of Shigellosis, Salmonello-sis, Escherichiosis at 420 yearly age children were per-formed. Its characterized by hight percent of gastroentero-colitic forms, vomiting, ketoacidosis, and dehydratation on presentation. The clinical values of ultrasonic investigations of haemodynamic indexes were investigated. It was pro-posed to add ultrasonic haemodynamic indexes to standards of treatment of severe form of intestinal infectious diseases at children.
Keywords: інфекційні хвороби; кишкові інфекції; діти; терапія